Negative body image components as risk factors for orthorexia nervosa: Prospective findings. (1st November 2022) - Messer, Mariel; Liu, Claudia; McClure, Zoe; Mond, Jasmin; Tiffin, Catherine; Linardon, Jake
Abstract: Emerging theoretical and empirical evidence indicates that negative body image might be implicated in the onset or maintenance of ON symptoms. However, existing research investigating associations between negative body image and ON is limited to cross-sectional designs and has failed to consider the independent role of distinct components of body image. To overcome these limitations, the present study examined the prospective associations between five components of body image (i.e., overvaluation, dissatisfaction, preoccupation, body checking, and body image avoidance) and ON symptoms in community-based adult women. Participants were assessed at baseline and at a three-month follow-up, with 558 women included in the final analyses. After adjusting for baseline ON symptoms, higher scores on each of the five body image components at baseline significantly predicted greater increases in ON symptoms in univariate analyses. However, in multivariate analyses, overvaluation with weight and shape was the only component of body image to uniquely predict ON symptoms. Findings suggest that certain components of negative body image may increase the risk for ON symptoms. Findings also lend support to recent proposals that ON may be better viewed as a variant of an existing eating disorder, given that both appear to share similar underlying risk factors.